Studies in the history of culture and science : a tribute to Gad Freudenthal - Fontaine, Resianne, 1953-; Freudenthal, Gad (Studies in Jewish history and culture ;, 2011)
An hommage to Gad Freudenthal, this volume offers twenty-two chapters on the history of science and the role of science in Jewish cultures. Written by outstanding scholars from all over the world it is a token of appreciation for Freudenthal's accomplishments in this discipline. The chapters in this volume include editions and translations of source texts in different languages and focus on topics that reflect the proble¿¿matiques Gad Freudenthal often tackled in his own research: aspects of knowledge transfer, translation processes and the appropriation of knowledge from one culture to another. They are contributions to a better understanding of the cross-cultural contacts in the field of science between Jews, Muslim and Christians in the Middle Ages and early modern times.